OPTIMALISASI PRODUKSI ALAT BERAT DALAM PEKERJAAN GALIAN DAN TANAMAN DI PROYEK JALAN RAYA (STUDI KASUS: JALUR LINTAS SELATAN LOT 2 BLITAR) - DANANG WIJANARKO; RANDY WIJAYA RAHMADI (JURNAL DAKTILITAS, 2024)
Abstrak The effectiveness and success of construction projects is greatly influenced by the productivity of heavy equipment, especially in terms of excavation work and road filling. Road projects include digging and building of embankments. assessing the output of different kinds of heavy machinery used in excavation projects is among this research's goals, and embankments, together with the elements that affect how well such heavy equipment. Operational efficiency of the heavy equipment. Bulldozers, dump trucks and excavators are some of the heavy equipment studied. Direct field observations and interviews with operators and project managers were used to collect productivity data. This research uses a quantitative descriptive analysis methodology, by calculating the volume of material transported by each heavy equipment in one unit of time. Analysis findings show that a number of variables, such as weather, operator skill, ground conditions, and equipment maintenance, influence machine productivity. When working on relatively soft ground, excavators have excellent productivity; however, when working on embankments, bulldozers are more efficient. Transport distance and road conditions have a major impact on dump truck productivity. The results in the field conclude that optimizing the use of heavy equipment is possible by choosing the appropriate tools. according to field conditions, adequate operator training, and routine maintenance of heavy equipment. Implementation of these findings is expected to increase the efficiency of road construction projects, reduce completion time, and reduce operational costs. Keywords: productivity of heavy equipment, excavations, embankments, excavators, dump trucks Abstrak Efektivitas dan keberhasilan proyek pembangunan sangat dipengaruhi oleh produktivitas alat berat, terutama dalam hal pekerjaan penggalian dan penimbunan jalan. Proyek jalan termasuk pekerjaan galian dan timbunan. Mengevaluasi produktivitas berbagai jenis alat berat yang digunakan dalam proyek penggalian adalah salah satu tumpukan, tujuan penelitian, dan faktor-faktor yang mempengaruhinya kinerja alat berat tersebut. Efisiensi operasional dari alat berat tersebut. Buldoser, dump truck, dan ekskavator adalah beberapa alat berat yang diteliti. Pengamatan langsung di lapangan dan wawancara dengan operator dan manajer proyek digunakan untuk mengumpulkan data produktivitas. Penelitian ini menggunakan metodologi analisis deskriptif kuantitatif, dengan menghitung volume material yang diangkut oleh setiap alat berat dalam satu unit waktu. Temuan analisis menunjukkan bahwa sejumlah variabel, seperti cuaca, keterampilan operator, kondisi tanah, dan pemeliharaan peralatan, mempengaruhi produktivitas alat berat. Ketika bekerja di tanah yang relatif lunak, excavator memiliki produktivitas yang sangat baik; namun, ketika bekerja di tanggul, buldoser lebih efisien. Jarak angkut dan kondisi jalan memiliki dampak besar pada produktivitas dump truck. Hasil di lapangan menyimpulkan bahwa optimalisasi penggunaan alat berat dapat dicapai dengan pemilihan alat yang tepat sesuai dengan kondisi lapangan, pelatihan operator yang memadai, serta pemeliharaan rutin alat berat. Implementasi temuan ini diharapkan dapat meningkatkan efisiensi proyek konstruksi jalan, mengurangi waktu penyelesaian, dan menekan biaya operasional. Kata kunci: produktivitas alat berat, galian, timbunan, excavator, dump truck